Объяснение:
(2x+c)(y+k)=2xy+2xk+cy+ck
(a-2b)(x+y)=ax+ay-2bx-2by
(a-x)(2b-y)=2ab-ay-2bx+xy
(x+8)(5y-1)=5xy-x+40y-8
(b-3)(5a-2)=5ab-2b-15a+6
(-a+y)(-1-y)=a+ay-y-y²
(2y-1)(3y+2)=6y²+4y-3y-2
(5x-3)(4-3x)=20x-15x²-12+9x
(x²+y)(x+y²)=x³+x²y²+xy+y³
(5x²-4x)(x+1)=5x³+5x²-4x²-4x
(x²+xy-y²)(3x+y)=3x³+x²y+3x²y+xy²-3xy²-y³
(3y-4)(y²-y+1)=3y³-3y²+3y-4y²+4y-4
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Объяснение:
(2x+c)(y+k)=2xy+2xk+cy+ck
(a-2b)(x+y)=ax+ay-2bx-2by
(a-x)(2b-y)=2ab-ay-2bx+xy
(x+8)(5y-1)=5xy-x+40y-8
(b-3)(5a-2)=5ab-2b-15a+6
(-a+y)(-1-y)=a+ay-y-y²
(2y-1)(3y+2)=6y²+4y-3y-2
(5x-3)(4-3x)=20x-15x²-12+9x
(x²+y)(x+y²)=x³+x²y²+xy+y³
(5x²-4x)(x+1)=5x³+5x²-4x²-4x
(x²+xy-y²)(3x+y)=3x³+x²y+3x²y+xy²-3xy²-y³
(3y-4)(y²-y+1)=3y³-3y²+3y-4y²+4y-4